Estudio térmico de alternativa de ladrillo no estructural basado en los residuos de construcción y demolición (RCD). Zona de la Samaria de Ibagué Tolima (2022)
The present experimental research seeks to make a product based on construction and demolition waste CDW, in which it is demonstrated from a compressed earth block CEB and applications and incidences in the field of construction. In addition, it delves into the area of incidences and thermal behavior in order to respond in some way to the needs of new trends in bioclimatic architecture and sustainable architecture. The project is developed in order to promote and propose a way to reduce the CDW generated by the construction industry, in this case working with waste from the area known as La Samaria in the city of Ibagué, Tolima. The vision of the product is focused on the use and commercialization at national level being a pioneer in the market of sustainable and bioclimatic constructions, helping to reduce the carbon footprint generated by the construction industry